Heat-resistant and high-impedance BM photoresist based on copolymer grafted modified carbon black and preparation method of heat-resistant and high-impedance BM photoresist

By oxidative modification of carbon black and surface graft copolymerization, polyimide resin was introduced to prepare high-impedance BM photoresist, which solved the problem of insufficient performance of traditional BM photoresist in 8K display technology, and achieved high resolution, high optical density and strong heat resistance.

CN119717392AActive Publication Date: 2025-03-28WANSIDE NEW MATERIAL TECH (ZHONGSHAN) CO LTD

Patent Information

Application Number
CN202411861187.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-28
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

Traditional BM photoresist is difficult to meet the requirements of high resolution, high optical density, high surface resistance and strong heat resistance in 8K display technology, and unmodified carbon black is prone to failure when cured at high temperature, resulting in reduced surface impedance and peeling.

Method used

The carbon black is modified by an oxidant and a chlorinating agent, acrylic or methacrylic acid, anhydride, initiator and catalyst are introduced, surface graft copolymerization is carried out, and polyimide resin is introduced on the copolymer chain to prepare surface modified carbon blacks of acrylic-co-imide or methacrylic-co-imide graft copolymer.

Benefits of technology

The heat resistance and dispersion stability of carbon black are improved, the high impedance, light shielding and high temperature resistance of BM photoresist are enhanced, and the stable performance under high temperature conditions of 230-270℃ is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005193240520000041
    Figure BDA0005193240520000041
  • Figure BDA0005193240520000042
    Figure BDA0005193240520000042
  • Figure BDA0005193240520000051
    Figure BDA0005193240520000051
Patent Text Reader

Abstract

The invention relates to a heat-resistant high-impedance BM photoresist based on copolymer grafted modified carbon black and a preparation method thereof, and belongs to the technical field of photoresist materials. Carbon black is subjected to oxidation modification, a chlorinating agent is added to chloridize oxidized carbon black, and active controllable free radicals are introduced to the surface of chlorinated carbon black, so that a copolymer is grafted to the surface of the carbon black; and finally, the acrylic acid-co-imide grafted copolymer surface modified carbon black or methacrylic acid-co-imide grafted copolymer surface modified carbon black with strong heat resistance is obtained. The high-impedance BM photoresist prepared from the modified carbon black can provide relatively strong static electricity and space stabilization effects, and the dispersion stability of the carbon black in resin is also improved; in addition, the copolymer is grafted with a polyimide chain, so that the copolymer has strong temperature resistance and corrosion resistance. By using the graft copolymer surface-modified carbon black, a high-impedance BM photoresist having a high OD value, high insulativity, excellent heat resistance, and high-fineness pattern linearity can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photoresist materials, and in particular relates to surface-modified carbon black and a preparation method thereof, and a high-impedance and high-temperature-resistant BM photoresist and a preparation method thereof. Background Art

[0002] 8K (7680×4320) is the highest resolution frequency that digital video can currently achieve, and the 8K screen is the highest-definition display carrier. This carrier provides a good display platform for high-definition movie-level camcorders and is a necessary means of displaying ultra-high-definition film and television. The color display of traditional liquid crystal displays (LCDs) is achieved through color filters. Among them, BM (Black Matrix) photoresist is the black matrix in the filter. Its main function is to isolate the color photoresist to prevent color mixing, and another important function is to shield light to achieve black display. However, due to the limitations of traditional technology, its optical density (OD) value has always remained at 2.8-3.5 / μm, which usually causes light leakage on the screen. However, with the rapid development of high-precision 8K display technology, there is an urgent need to contain a higher density of black pigment in BM photoresist to prevent light leakage. But at the same time, too high a pigment concentration can easily weaken the insulation of the photoresist. In addition, BM photoresist prepared with ordinary unmodified carbon black is prone to failure due to its inability to withstand high temperatures (230-270°C) during curing, which ultimately leads to a decrease in its surface impedance and significant peeling. Therefore, there is an urgent need for a new type of "high light-shielding, strong impedance, and high temperature resistance" BM photoresist that can balance performance.

[0003] Carbon black is a commonly used black pigment in BM photoresist. It is composed of quasi-graphite structural units, and the arrangement of quasi-graphite sheets is relatively disordered. Carbon black aggregates have a large specific surface area and abundant polar groups on the surface. The cohesion between particles is very strong, so there are problems such as difficulty in dispersion and easy flocculation in the matrix, which affects the compatibility of carbon black particles and the physical and chemical properties of composite materials.

[0004] At present, there are few reports on the surface modification of carbon black used in BM photoresist, and the existing carbon black surface treatment technology is difficult to simultaneously meet the requirements of BM photoresist for 8K display for high resolution, high optical density, high surface resistance and strong heat resistance. In response to the above problems, we proposed a new technical solution. Summary of the invention

[0005] The present invention firstly oxidizes and modifies untreated carbon black by an oxidant; then adds a chlorinating agent to chlorinate the oxidized carbon black, and introduces acrylic acid or methacrylic acid, anhydride containing stable free radicals, an initiator, and a catalyst on the surface of the chlorinated carbon black, and initiates a primary graft copolymerization on the surface of the carbon black for further treatment; after the reaction is successful, a polyimide resin is secondary grafted on the copolymer chain to finally obtain an acrylic acid-co-imide graft copolymer surface-modified carbon black or a methacrylic acid-co-imide graft copolymer surface-modified carbon black. The carboxyl-containing photosensitive resin, the surface-modified carbon black, the photoinitiator, the multifunctional monomer, and the fourth solvent are uniformly mixed to obtain a mixture, and then the mixture is further ground by a nano-grinder to make the particle size of the mixture 50-80nm, so as to obtain a high-impedance BM photoresist.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] The heat-resistant high-impedance BM photoresist based on copolymer grafted modified carbon black comprises the following raw materials in parts by weight: 25 parts by weight of a carboxyl-containing photosensitive resin, 20 to 30 parts by weight of acrylic polymer surface-modified carbon black, 0.1 to 3 parts by weight of a photoinitiator, 1 to 20 parts by weight of a multifunctional monomer, and 150 to 400 parts by weight of a fourth solvent.

[0008] As a preferred technical solution of the present invention, the carboxyl-containing photosensitive resin is one of acrylic resin, epoxy-modified acrylic resin, polyester-modified acrylic resin, bisphenol fluorene-modified acrylic resin, polyurethane acrylic resin, silicone-modified acrylic resin, and polyamide-modified acrylic resin.

[0009] As a preferred technical solution of the present invention, the acrylic polymer surface-modified carbon black is an acrylic acid-co-imide graft copolymer surface-modified carbon black or a methacrylic acid-co-imide graft copolymer surface-modified carbon black, and the preparation method comprises the following steps:

[0010] S1. Heat, stir and reflux carbon black, an oxidant and a first solvent under nitrogen protection for 5 to 8 hours, filter, wash with deionized water until neutral and then vacuum dry to obtain oxidized carbon black;

[0011] S2, stirring and refluxing oxidized carbon black, a chlorinating agent, and a second solvent at 15-25° C. for 1-3 hours, removing excess chlorinating agent and solvent by rotary evaporation, adding the second solvent, the first initiator, a comonomer, and a polymerization catalyst again, continuously introducing nitrogen for 30-90 minutes, heating, stirring, and refluxing for 12-18 hours, filtering the slurry, and vacuum drying to obtain an acrylic acid-co-anhydride copolymer surface-modified carbon black or a methacrylic acid-co-anhydride copolymer surface-modified carbon black;

[0012] S3. Add acrylic acid-co-anhydride copolymer surface-modified carbon black or methacrylic acid-co-anhydride copolymer surface-modified carbon black, grafted resin and acid binding agent into the third solvent, stir and react at 40-60° C. for 1-3 hours, filter the slurry, and vacuum dry to obtain acrylic acid-co-imide grafted copolymer surface-modified carbon black or methacrylic acid-co-imide grafted copolymer surface-modified carbon black.

[0013] As a preferred technical solution of the present invention, the carbon black in step S1 has an oil absorption value DBP of 30 to 100 ml / 100 g and a specific surface area of ​​30 to 150 m 2 / g; the oxidant is one of formaldehyde, hydrogen peroxide solution, sulfuric acid, nitric acid, acidic potassium permanganate solution, potassium dichromate solution, and saturated potassium persulfate solution; the first solvent is one of anhydrous ethanol, methanol, ethyl acetate, and dichloromethane.

[0014] As a preferred technical solution of the present invention, the chlorinating agent in step S2 is one of dichlorothionyl, phosphorus trichloride, phosphorus pentachloride, and sulfuryl chloride; the second solvent is one of tetrahydrofuran, methanol, toluene, xylene, dioxane, anisole, dimethyl sulfoxide, methanol, and acetonitrile; the first initiator is one of 3-hydroxy-2,2-dimethylpropionic acid-3-hydroxy-2,2-dimethylpropyl ester, 2-bromo-2-methylpropionic acid 3-(trichlorosilyl)propyl ester, and 2-bromo-N-[2-(3,4-dihydroxyphenyl)ethyl]propionamide of organic halides; the comonomer includes a first comonomer and a second comonomer, the first comonomer is one of acrylic acid and methacrylic acid, and the second comonomer is an acid anhydride capable of forming stable free radicals, and its structure is one of Chemical Formula 1 and Chemical Formula 2; the polymerization catalyst is one of copper salts selected from copper bromide, cuprous bromide, ferric bromide, ferric chloride, and ferric chloride hexahydrate;

[0015]

[0016] Among them, R1 and R2 represent one of hydrogen atom, methyl group, chlorine atom, phenyl group and phosphorus heterocyclic group respectively; R3 and R4 represent one of hydrogen atom, methyl group, chlorine atom and phenyl group respectively.

[0017] As a preferred technical solution of the present invention, the grafted resin in step S3 is polyimide, and the structural formula is one of the chemical formulas 3-7; the acid binding agent is one of 4-dimethylaminopyrimidine, triethylamine, sodium carbonate and potassium carbonate; the third solvent is one of N,N-dimethylformamide, tetrahydrofuran, N,N-dimethylacetamide and N-methylpyrrolidone;

[0018]

[0019]

[0020] Among them, n is 300~800.

[0021] As a preferred technical solution of the present invention, the photoinitiator is one of a triazine compound, a biimidazole compound, an acetophenone compound, an oxime ester compound, a benzophenone compound, a thioxanthone compound, and a phosphine oxide compound.

[0022] As a preferred technical solution of the present invention, the multifunctional monomer is one of 1,6-hexanediol diacrylate, ethylene glycol diacrylate, neopentyl glycol diacrylate, triethylene glycol diacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate.

[0023] As a preferred technical solution of the present invention, the fourth solvent is one of propylene glycol monomethyl ether acetate, ethyl lactate, propylene glycol monomethyl ether, 3-ethoxyethyl propionate, ethylene glycol monomethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, 3-methoxybutyl acetate, 3-methoxy-1-butanol, 4-hydroxy-4-methyl-2-pentanone, N,N-dimethylformamide, and N-methylpyrrolidone.

[0024] Furthermore, the method for preparing the heat-resistant high-impedance BM photoresist based on copolymer grafted modified carbon black comprises the following steps:

[0025] (1) uniformly mixing a carboxyl-containing photosensitive resin, acrylic polymer surface-modified carbon black, a photoinitiator, a multifunctional monomer, and a fourth solvent to obtain a mixture;

[0026] (2) The mixture is further ground by a nano-grinder to obtain a particle size of 50 to 80 nm, thereby obtaining a high-impedance BM photoresist.

[0027] Beneficial effects of the present invention:

[0028] (1) The present invention provides a surface-modified carbon black, which first uses an oxidant such as hydrogen peroxide solution and formaldehyde to oxidize the surface of carbon black to increase the surface oxygen content and make the surface of carbon black rich in active hydrogen; then, an initiator is used to introduce active controllable free radicals on the surface of carbon black to graft copolymers on the surface of carbon black; then, the active groups on the side chains of the copolymer are used to secondary graft polyimide chains with strong heat resistance on the surface of carbon black.

[0029] (2) The present invention also provides a high-impedance BM photoresist prepared by surface-modified carbon black. The high-impedance BM photoresist has a strong electrostatic and steric stabilizing effect provided by the acrylic acid-co-imide or methacrylic acid-co-imide copolymer grafted on the surface of the carbon black, thereby improving the dispersion stability of the carbon black in the resin. In addition, the polyimide chain grafted on the copolymer has strong temperature resistance and corrosion resistance, thereby improving the heat resistance and chemical resistance of the carbon black during the resin curing process.

[0030] (3) The present invention can obtain a high-impedance BM photoresist with a high OD value, high insulation, excellent heat resistance, and high-definition pattern linearity by using surface-modified carbon black. DETAILED DESCRIPTION

[0031] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0032] The untreated carbon black in the following embodiments and comparative examples can be selected from PRINTEX-U, PRINTEX-V, PRINTEX-140U, PRINTEX-140V, PRINTEX-95, PRINTEX-85, PRINTEX-75, PRINTEX-55, PRINTEX-45, PRINTEX-300, PRINTEX-35, PRINTEX-25, PRINTEX-200, PRINTEX-40, PRINTEX-30, PRINTEX-3, PRINTEX-A, PRINTEX-BLACK-550, PRINTEX-BLACK-350, SPECIAL BLACK-250, SPECIAL BLACK-250, SPECIAL BLACK-100 and LAMP BLACK-101 of Mitsubishi Heavy Industries, Ltd. of Japan; diagram black II, diagram black N339, diagram black SH, diagram black H, diagram black LH, diagram black LA, diagram black SF, diagram black N550M, diagram black M, diagram black E, diagram black G, diagram black R, diagram black N760M, diagram black LR, #2700, #2600, #2400, #2350, #2300, #2200, #1000, #980, #900, MCF88, #52, #50, #47, #45, #45L, #25, #CF9, #95, #3030, #3050, MA7, MA77, MA8;RAVEN-1100ULTRA, RAVEN-1080ULTRA, RAVEN-1060ULTRA, RAVEN-1040, RAVEN-1035, RAVEN-1020, RAVEN-1000, RAVEN-890H, RAVEN-890, RAVEN-880ULTRA, RAVEN-860ULTRA, RAVEN-850, RAVEN-820, RAVEN-790ULTRA, RAVEN-780ULTRA, RAVEN-760ULTRA, RAVEN-520, RAVEN-500, RAVEN RAVEN-460, RAVEN-450, RAVEN-430ULTRA, RAVEN-420, RAVEN-410, RAVEN-2500ULTRA, RAVEN-2000, RAVEN-1500, RAVEN-1255, RAVEN-1250, RAVEN-1200, RAVEN-1190ULTRA and RAVEN-1170; the photoinitiator can be selected from triazine compounds: 2-(4-methoxyphenyl)-4,6-bis(trichloromethyl)-S-triazine, 2,4-bis(trichloromethyl)-6-p-methoxyphenyl-S-triazine and 2-(3,4-dimethoxyphenyl)-4,6-bis(trichloromethyl)-S-triazine. chloromethyl)-1,3,5-triazine, biimidazole compounds: 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetraphenyldiimidazole, 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-diimidazole, acetophenone compounds: 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-1-one, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 1-hydroxycyclohexyl phenyl ketone, 2,2-dimethoxy-2-phenylacetophenone, 2-methyl-(4-methylthiophenyl)-2-morpholin-one and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1 -ketone, oxime ester compounds: 1-[4-(phenylthio)phenyl]-1,2-octanedione-2-(O-benzoyloxime) and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone 1-(O-acetyloxime), benzophenone compounds: 4,4'-bis(dimethylamino)benzophenone and 4,4'-bis(diethylamino)benzophenone, thioxanthone compounds: 2,4-diethylthioxanthone, 2-chlorothioxanthone, isopropylthioxanthone and 2-isopropylthioxanthone, phosphine oxide compounds: 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide and bis(2,6-xylyl)phosphoryl chloride. ;

[0033] Modification Example 1

[0034] Preparation of oxidized carbon black:

[0035] Take 300 g of carbon black PRINTEX-U and 5 L of 30% hydrogen peroxide solution into a three-necked flask with a reflux condenser, start the stirrer, heat to 65°C to react for 6 hours, then filter and dry at 100°C to obtain oxidized carbon black.

[0036] Modification Example 2

[0037] Preparation of oxidized carbon black:

[0038] Take 300 g of carbon black PRINTEX-U and 3 L of 70% concentrated sulfuric acid into a three-necked flask with a reflux condenser, start the stirrer, heat to 65°C to react for 6 hours, then filter and dry at 100°C to obtain oxidized carbon black.

[0039] Synthesis Example 3-8

[0040] Preparation of acrylic polymer surface modified carbon black:

[0041] First, 30 parts by weight of oxidized carbon black, 196.56 parts by weight of chlorinating agent (dichlorothionyl, hereinafter referred to as F-1) and 106.8 parts by weight of the second solvent (tetrahydrofuran, hereinafter referred to as THF) were added to a three-necked flask with a reflux condenser, and the agitator was started. Stirring and reflux reaction were carried out at room temperature for 1 hour. After the reaction was completed, the excess chlorinating agent and solvent were removed by rotary evaporation. After being spin-dried, 10 parts by weight of the first comonomer (acrylic acid, hereinafter referred to as AA), 11.8 parts by weight of the second comonomer (2,3-diphenylmaleic anhydride or cis-4-cyclohexene-1,2-dicarboxylic anhydride, hereinafter referred to as S-1 or S-2, respectively), 79.2 parts by weight of the first initiator 3-hydroxy-2,2-dimethylpropionic acid-3-hydroxy-2,2-dimethylpropyl ester, hereinafter referred to as Br-1] and 1.34 parts by weight of polymerization catalyst (copper bromide, hereinafter referred to as C-1) were taken respectively, and nitrogen was continuously introduced for 30 minutes to replace the air in the bottle. The reaction system was heated to 60°C and stirred, and the reaction was refluxed for at least 12 hours. After the reaction was completed, the slurry was filtered to obtain the acrylic acid-co-anhydride copolymer surface-modified carbon black.

[0042] Then, the surface-modified carbon black of the acrylic acid-co-anhydride copolymer obtained above, 20 parts by weight of the grafted resin (respectively shown in the chemical formula 3 or 5 or 7, wherein n is 800, hereinafter referred to as X-1 or X-2 or X-3), 0.2 parts by weight of the acid-binding agent (4-dimethylaminopyrimidine, hereinafter referred to as DAMP), and 60 parts by weight of the third solvent (N,N-dimethylformamide, hereinafter referred to as DMF) were added to a three-necked flask with a reflux condenser, the stirrer was started, and the mixture was stirred and refluxed at 60°C for 1 hour, and the slurry was filtered. Finally, the acrylic acid polymer surface-modified carbon black in Synthesis Example 3-8 was obtained by vacuum drying. The types and amounts of each raw material in Synthesis Example 3-8 are shown in Table 1.

[0043] Table 1

[0044]

[0045]

[0046] Comparison example

[0047] In control example 9, unmodified carbon black PRINTEX-U was used to replace the acrylic polymer surface-modified carbon black; in control example 10, the oxidized carbon black in modification example 1 was used to replace the acrylic polymer surface-modified carbon black.

[0048] Example 11-18 Preparation of BM photoresist:

[0049] Take 20 parts by weight of the acrylic polymer surface-modified carbon black in the above-mentioned synthesis examples 3-8, 25 parts by weight of bisphenol A modified acrylic resin (KBR-101, purchased from KISCO, South Korea), 0.37 parts by weight of photoinitiator 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone 1-(0-acetyl-oxime) (hereinafter referred to as Y-1), 6.25 parts by weight of multifunctional monomer (dipentaerythritol hexaacrylate, hereinafter referred to as DPHA) and 212.5 parts by weight of the fourth solvent (propylene glycol monomethyl ether acetate, hereinafter referred to as PGMEA), mix and disperse them evenly to obtain a uniform black mixture, which are BM photoresists 11-16 respectively. Then, 20 parts by weight of the above-mentioned control example 9 or control example 10, 25 parts by weight of bisphenol fluorene modified acrylic resin (KBR-101, purchased from KISCO, South Korea), 0.37 parts by weight of photoinitiator 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone 1-(0-acetyl-oxime) (hereinafter referred to as Y-1), 6.25 parts by weight of multifunctional monomer (dipentaerythritol hexaacrylate, hereinafter referred to as DPHA) and 212.5 parts by weight of the fourth solvent (propylene glycol monomethyl ether acetate, hereinafter referred to as PGMEA) were mixed and dispersed uniformly to obtain a uniform black mixture, which was BM photoresist 17 or BM photoresist 18 respectively. Finally, the dispersibility of the photoresist was measured using a particle size analyzer (Zetasizepro, produced by Malvern). The type and amount of the photoresist raw materials and the average particle size of the photoresist are shown in Table 2.

[0050] Table 2

[0051]

[0052]

[0053] Performance Evaluation

[0054] First, the particle size analysis of the BM photoresists 11-18 in the above-mentioned embodiments was performed using a particle size analyzer; then, they were uniformly coated on a glass substrate coated with ITO by spin coating. After drying at 90°C for 5 minutes, the photoresists were exposed through a photomask with a pattern using an exposure machine with a wavelength of 365nm LED light source, and then developed with a 0.5wt% Na2CO3 aqueous solution. Finally, the coatings were thermally cured at 230°C, 250°C, and 270°C for 30 minutes, respectively. The coatings obtained were used for the following evaluations.

[0055] (1) Surface resistance

[0056] Using a high resistance meter (6517B, produced by Keithley) with an 8009 fixture, the surface resistance values ​​of the coatings of BM photoresists 11-18 after curing at 230°C, 250°C, and 270°C were measured under a voltage of 1000V (the results are shown in Table 3).

[0057] (2) OD value

[0058] The transmittance of each substrate at 550 nm was measured using a spectrophotometer (UV-2700, produced by Shimadzu Corporation), and the OD values ​​of each coating after curing of BM photoresists 11-18 at 230°C, 250°C, and 270°C were obtained (the results are shown in Table 3).

[0059] Table 3

[0060]

[0061]

[0062] As shown in the results in Table 3, the BM photoresists 11-16 formed by the acrylic polymer surface modified carbon black have high resistance and high OD values, and such performance remains stable under high temperature curing conditions of 230-270°C. The BM photoresists 17 and 18 formed by the unmodified carbon black and oxidized carbon black control examples have lower resistance and OD values, and their performance decreases significantly as the curing temperature increases. The results show that the surface impedance, light shielding and high temperature resistance of carbon black as a BM photoresist can be significantly enhanced after being grafted and modified by copolymers.

[0063] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any indirect modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. Heat-resistant high-impedance BM photoresist based on copolymer grafted modified carbon black, characterized by: The invention comprises the following raw materials in parts by weight: 25 parts by weight of a carboxyl-containing photosensitive resin, 20 to 30 parts by weight of acrylic polymer surface-modified carbon black, 0.1 to 3 parts by weight of a photoinitiator, 1 to 20 parts by weight of a multifunctional monomer, and 150 to 400 parts by weight of a fourth solvent.

2. The heat-resistant high-impedance BM photoresist based on copolymer grafted modified carbon black according to claim 1, characterized in that: The carboxyl-containing photosensitive resin is one of acrylic resin, epoxy-modified acrylic resin, polyester-modified acrylic resin, bisphenol fluorene-modified acrylic resin, polyurethane acrylic resin, silicone-modified acrylic resin, and polyamide-modified acrylic resin.

3. The heat-resistant high-impedance BM photoresist based on copolymer grafted modified carbon black according to claim 1, characterized in that: The acrylic polymer surface-modified carbon black is an acrylic acid-co-imide graft copolymer surface-modified carbon black or a methacrylic acid-co-imide graft copolymer surface-modified carbon black, and the preparation method comprises the following steps: S1. Heat, stir and reflux carbon black, an oxidant and a first solvent under nitrogen protection for 5 to 8 hours, filter, wash with deionized water until neutral and then vacuum dry to obtain oxidized carbon black; S2, stirring and refluxing oxidized carbon black, a chlorinating agent, and a second solvent at 15-25° C. for 1-3 hours, removing excess chlorinating agent and solvent by rotary evaporation, adding the second solvent, the first initiator, a comonomer, and a polymerization catalyst again, continuously introducing nitrogen for 30-90 minutes, heating, stirring, and refluxing for 12-18 hours, filtering the slurry, and vacuum drying to obtain an acrylic acid-co-anhydride copolymer surface-modified carbon black or a methacrylic acid-co-anhydride graft copolymer surface-modified carbon black; S3. Add acrylic acid-co-anhydride copolymer surface-modified carbon black or methacrylic acid-co-anhydride graft copolymer surface-modified carbon black, graft resin and acid binding agent into the third solvent, stir and react at 40-60° C. for 1-3 hours, filter the slurry, and vacuum dry to obtain acrylic acid-co-imide graft copolymer surface-modified carbon black or methacrylic acid-co-imide graft copolymer surface-modified carbon black.

4. The heat-resistant high-impedance BM photoresist based on copolymer grafted modified carbon black according to claim 1, characterized in that: The carbon black in step S1 has an oil absorption value DBP of 30 to 100 ml / 100 g and a specific surface area of ​​30 to 150 m 2 / g; the oxidant is one of formaldehyde, hydrogen peroxide solution, sulfuric acid, nitric acid, acidic potassium permanganate solution, potassium dichromate solution, and saturated potassium persulfate solution; the first solvent is one of anhydrous ethanol, methanol, ethyl acetate, and dichloromethane.

5. The heat-resistant high-impedance BM photoresist based on copolymer grafted modified carbon black according to claim 1, characterized in that: The chlorinating agent in step S2 is one of thionyl chloride, phosphorus trichloride, phosphorus pentachloride, and sulfuryl chloride; the second solvent is one of tetrahydrofuran, methanol, toluene, xylene, dioxane, anisole, dimethyl sulfoxide, methanol, and acetonitrile; the first initiator is one of organic halides such as 3-hydroxy-2,2-dimethylpropionic acid-3-hydroxy-2,2-dimethylpropyl ester, 2-bromo-2-methylpropionic acid 3-(trichlorosilyl)propyl ester, and 2-bromo-N-[2-(3,4-dihydroxyphenyl)ethyl]propionamide; the comonomer includes a first comonomer and a second comonomer, the first comonomer is one of acrylic acid and methacrylic acid, and the second comonomer is an acid anhydride capable of forming stable free radicals, and its structure is one of Chemical Formula 1 and Chemical Formula 2; the polymerization catalyst is one of copper bromide, cuprous bromide, ferric bromide, ferric chloride, and ferric chloride hexahydrate; Among them, R1 and R2 represent one of hydrogen atom, methyl group, chlorine atom, phenyl group and phosphorus heterocyclic group respectively; R3 and R4 represent one of hydrogen atom, methyl group, chlorine atom and phenyl group respectively.

6. The heat-resistant high-impedance BM photoresist based on copolymer grafted modified carbon black according to claim 1, characterized in that: The grafted resin in step S3 is polyimide, and the structural formula is one of the chemical formulas 3-7; the acid-binding agent is one of 4-dimethylaminopyrimidine, triethylamine, sodium carbonate and potassium carbonate; the third solvent is one of N,N-dimethylformamide, tetrahydrofuran, N,N-dimethylacetamide and N-methylpyrrolidone; Among them, n is 300~800.

7. The heat-resistant high-impedance BM photoresist based on copolymer grafted modified carbon black according to claim 1, characterized in that: The photoinitiator is one of triazine compounds, biimidazole compounds, acetophenone compounds, oxime ester compounds, benzophenone compounds, thioxanthone compounds and phosphine oxide compounds.

8. The heat-resistant high-impedance BM photoresist based on copolymer grafted modified carbon black according to claim 1, characterized in that: The multifunctional monomer is one of 1,6-hexanediol diacrylate, ethylene glycol diacrylate, neopentyl glycol diacrylate, triethylene glycol diacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate.

9. The heat-resistant high-impedance BM photoresist based on copolymer grafted modified carbon black according to claim 1, characterized in that: The fourth solvent is one of propylene glycol monomethyl ether acetate, ethyl lactate, propylene glycol monomethyl ether, 3-ethoxyethyl propionate, ethylene glycol monomethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, 3-methoxybutyl acetate, 3-methoxy-1-butanol, 4-hydroxy-4-methyl-2-pentanone, N,N-dimethylformamide, and N-methylpyrrolidone.

10. The method for preparing a heat-resistant high-impedance BM photoresist based on copolymer grafted modified carbon black according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) uniformly mixing a carboxyl-containing photosensitive resin, acrylic polymer surface-modified carbon black, a photoinitiator, a multifunctional monomer, and a fourth solvent to obtain a mixture; (2) The mixture is further ground by a nano-grinder to obtain a particle size of 50 to 80 nm, thereby obtaining a high-impedance BM photoresist.

Citation Information

Patent Citations

  • Hybrid carbon black and coating composition

    CN106556970A

  • Surface modified carbon black and preparation method thereof, and high-impedance BM photoresist and preparation method thereof

    CN115011145A

  • Carbon black dispersion for black matrix, resist composition containing carbon black dispersion and application of resist composition

    CN117986897A

  • Black coating film composition, resin black matrix, color filter, and liquid crystal display

    JP2005075965A

  • Carbon black dispersion composition for black matrix

    KR100631861B1

Cited By

  • BM photoresist with interpenetrating cross-linked network structure and preparation method of BM photoresist

    CN122239369A

  • Interpenetrating network structure BM photoresist and preparation method thereof

    CN122239369B